How to Keep Employees Motivated During Covid-19 - Petra Holendová (Communications of International Proceedings, 2021)
The purpose of the article is to provide an overview of the original ideas and theoretical approaches in the field of employee motivation in the time of COVID-19. Methodology / methods: A comprehensive review of the most cited scientific literature and articles published in 2020 was performed. Scientific objective: In addition to health concerns, the COVID-19 pandemic has caused an economic and social crisis that has hit the service sector hard. Due to security measures, employers have been advised and instructed in certain sectors to allow their employees to work remotely. This article aims to write about the effectiveness of leadership and how to keep employees motivated during COVID-19 Findings: Workers' motivation naturally weakens during the Covid-19 era as the number of depressions among employees increases. It is very important not to underestimate these factors and work with them and motivate employees not only in cash but also in non-cash. Research has shown what kind of non-monetary instruments we can have. Conclusion: The paper provides effective suggestions on how to improve the motivation of employees in the time of COVID-19 and is then the basis for research in the current state of management in companies with organizational structure undergoing the project.
Keywords: COVID; Employees; Manamement; Motivation